2017
DOI: 10.1073/pnas.1620830114
|View full text |Cite
|
Sign up to set email alerts
|

Evolving polycentric governance of the Great Barrier Reef

Abstract: A growing field of sustainability science examines how environments are transformed through polycentric governance. However, many studies are only snapshot analyses of the initial design or the emergent structure of polycentric regimes. There is less systematic analysis of the longitudinal robustness of polycentric regimes. The problem of robustness is approached by focusing not only on the structure of a regime but also on its context and effectiveness. These dimensions are examined through a longitudinal ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 41 publications
0
122
0
Order By: Relevance
“…Polycentricity is often implicitly portrayed as a static attribute of governance systems despite its dynamic character (Galaz et al 2012). To conceive action situations as having a temporal imprint allows analyzing the evolution of interactions in polycentric governance systems over time, including the emergence of new governance spaces and the termination of others (Morrison 2017). In our ABSL analysis, the "land deal setup" action situation is terminated after agreements are concluded, and the "project implementation" starts with initial land conversion (Fig.…”
Section: Methodological Reflectionmentioning
confidence: 99%
“…Polycentricity is often implicitly portrayed as a static attribute of governance systems despite its dynamic character (Galaz et al 2012). To conceive action situations as having a temporal imprint allows analyzing the evolution of interactions in polycentric governance systems over time, including the emergence of new governance spaces and the termination of others (Morrison 2017). In our ABSL analysis, the "land deal setup" action situation is terminated after agreements are concluded, and the "project implementation" starts with initial land conversion (Fig.…”
Section: Methodological Reflectionmentioning
confidence: 99%
“…The boundary between the two jurisdictions is unclear because they define "low water mark" differently. The Great Barrier Reef Marine Park Act 1975 granted the federal government authority over the entire Great Barrier Reef region but the boundary difference was resolved by complementary zoning of adjacent state and federal marine parks (Day, 2016), an example of policy coherence in a polycentric governance system (Dale et al, 2016;Morrison, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Such systems have been identified as a means to address complex environmental problems (Biggs et al, 2012;Morrison, 2017), as independent government units may not be able to unilaterally resolve complex socioecological problems (Ostrom et al, 1961;Biggs et al, 2012). The success of polycentric governance systems in addressing environmental problems supports the need for policy coherence: complementary legislation that works between and within legislative sectors to achieve mutually-decided policy outcomes (Nilsson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, as many studies on neo-liberal nature (Heynen et al 2007;McCarthy and Prudham 2004) have shown, in an economic policy environment dominated by privatisation and deregulation, the efficacy of these institutions is challenged in many ways (also see Morrison 2017). As observed in 'green grabbing' studies (Fairhead et al 2012), in Colombo an 'environmental' pretext for wetlands was used to justify further appropriation of wetlands and eviction of low-income communities.…”
Section: The Anti-democratic Nature Of Wetland Appropriation Strategiesmentioning
confidence: 99%